2017
DOI: 10.1590/s0004-2803.201700000-05
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nutritional Status and the Clinical Outcomes of Patients With and Without Neoplasms According to Multiple Correspondence Analysis

Abstract: -Background -For many years, many studies have reported undesirable outcomes that may occur during the hospital stay of patients diagnosed with malnutrition or even at some nutritional risk. Objective -To investigate the relationship between nutritional status and clinical outcomes during hospital stay using the multiple correspondence analysis technique. Methods -This cross-sectional study included 600 patients with and without neoplasms. The following data were collected: subjective global assessment, nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This work also confirmed that users of DE departments are often characterised by poor dental follow-up [17][18][19] and are mostly from disadvantaged social backgrounds 12,21,31 . The MCA was chosen in the present study because it allows simultaneous analysis of all outcomes and characterised patients' profiles 33 . Whereas previous studies provided a general description of subjects who attended the DE department 12,[17][18][19]21,27,30,31 , this study aimed to highlight profiles of patients by linking sociodemographic characteristics to care-seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work also confirmed that users of DE departments are often characterised by poor dental follow-up [17][18][19] and are mostly from disadvantaged social backgrounds 12,21,31 . The MCA was chosen in the present study because it allows simultaneous analysis of all outcomes and characterised patients' profiles 33 . Whereas previous studies provided a general description of subjects who attended the DE department 12,[17][18][19]21,27,30,31 , this study aimed to highlight profiles of patients by linking sociodemographic characteristics to care-seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies provided a general description of subjects who attended the DE department 12,[17][18][19]21,27,30,31 , this study aimed to highlight profiles of patients by linking sociodemographic characteristics to care-seeking behaviours. The MCA was chosen in the present study because it allows simultaneous analysis of all outcomes and characterised patients' profiles 33 . This method led to the identification of two profiles of patients using the DE department, who were characterised by different motivations towards hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the sustained evidence that anthropometric and derived indicators are related to nutrition risk and undernutrition, 9‐12 previous data on the association of anthropometric and derived indicators with LOS are contradictory 1,10,13‐25 . Whereas in some studies an association between weight, triceps skinfold thickness (TST), mid‐upper arm circumference (MUAC), adductor pollicis muscle thickness (APMT), mid‐upper arm muscle area (AMA), mid‐upper arm muscle circumference (AMC), and body mass index (BMI) with longer LOS has been identified, 1,10,18‐23 in others these associations were not found 1,10,15,19‐26 . However, it is important to highlight that LOS may be influenced by many factors other than nutrition status—for instance, disease, age, and marital status 1,6,15,18,27 —and in some of the mentioned studies, the association between anthropometric and derived indicators with LOS was not adjusted for possible confounding variables 10,13,15,17,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in some studies an association between weight, triceps skinfold thickness (TST), mid‐upper arm circumference (MUAC), adductor pollicis muscle thickness (APMT), mid‐upper arm muscle area (AMA), mid‐upper arm muscle circumference (AMC), and body mass index (BMI) with longer LOS has been identified, 1,10,18‐23 in others these associations were not found 1,10,15,19‐26 . However, it is important to highlight that LOS may be influenced by many factors other than nutrition status—for instance, disease, age, and marital status 1,6,15,18,27 —and in some of the mentioned studies, the association between anthropometric and derived indicators with LOS was not adjusted for possible confounding variables 10,13,15,17,20 . Furthermore, the discharge destination was taken into account in only 1 study, and it was shown that MUAC was independently associated with LOS.…”
Section: Introductionmentioning
confidence: 99%
“…The results were considered statistically significant at p < 0.05. The correspondence between the STR locus typing and IHC and tumor markers was analyzed using multiple correspondence analysis, which is a multivariate statistical technique used to explore the simultaneous relationships between variables (Leandro-Merhi & JLB, 2017).…”
Section: Methodsmentioning
confidence: 99%